2013
DOI: 10.1021/jf403810y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Phenolic Content and Profile, Antioxidant Capacity, and Anti-inflammatory Bioactivity in Wild Alaskan and Commercial Vaccinium Berries

Abstract: Wild Alaskan Vaccinium berries, V. vitis-idaea (lowbush cranberry) and V. uliginosum (bog blueberry), were investigated in parallel to their commercial berry counterparts; V. macrocarpon (cranberry) and V. angustifolium (lowbush blueberry). Lowbush cranberry accumulated about twice the total phenolics (624.4 mg/100 g FW) and proanthocyanidins (278.8 mg/100 g) content as commercial cranberries, but A-type proanthocyanidins were more prevalent in the latter. Bog blueberry anthocyanin and total phenolic contents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
113
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(128 citation statements)
references
References 38 publications
13
113
1
1
Order By: Relevance
“…The higher anti-inflammatory activity of muscadine-SPI matrix can be attributed to higher total phenolic content of this ingredient. The anti-inflammatory activity of fruit and vegetable phytoactives has been previously described [19,20]. These results demonstrate that the fortified ingredient matrices, at reasonable dietary levels, contained phytoactives that suppressed activation of key pro-inflammatory genes triggered by an inflammatory stimulus.…”
Section: Bioactivity Of Phytoactives Bound To Matricessupporting
confidence: 66%
“…The higher anti-inflammatory activity of muscadine-SPI matrix can be attributed to higher total phenolic content of this ingredient. The anti-inflammatory activity of fruit and vegetable phytoactives has been previously described [19,20]. These results demonstrate that the fortified ingredient matrices, at reasonable dietary levels, contained phytoactives that suppressed activation of key pro-inflammatory genes triggered by an inflammatory stimulus.…”
Section: Bioactivity Of Phytoactives Bound To Matricessupporting
confidence: 66%
“…Previous studies of berries using similar analytical methods reported proanthocyanidin content (per 100 g FW) from 4.3 to 18.6 mg in aronia berry, 71.2 to 85.5 mg in blueberry, and 132.7 to 278.8 in cranberry (Grace, Esposito, Dunlap, & Lila, 2014;Taheri et al, 2013). Thus, AOB appears to have similar proanthocyanidin content to blueberry.…”
Section: Total Phenol and Proanthocyanidins Recovery From Aob Extractmentioning
confidence: 63%
“…V. angustifolium has been previously used for the treatment of diabetic symptoms, and it has been shown to exert a variety of physiological effects including antioxidant, anticancer, and anti-microbial effects (916). Methanol was found to be the most suitable solvent for the extraction of polyphenolic compounds from plant materials (25).…”
Section: Resultsmentioning
confidence: 99%
“…Among the Vaccinium genus, the lowbush blueberry, Vaccinium angustifolium , is native to Eastern and Central Canada, and the North East of the United States. This species has been used for the treatment of diabetic symptoms, and it is evidenced to possess a variety of physiological properties including anti-inflammatory, antioxidant, and anticancer activities (916). We previously reported that V. angustifolium root extract (VAE) inhibited A23187 and phorbol 12-myristate 13-acetate-induced degranulation via down-regulation of protein kinases C translocation (17).…”
Section: Introductionmentioning
confidence: 99%